Western Ghats: Biodiversity People - R J Ranjit Daniels; Jayshree Vencatesan; DANIELS (R J Ranjit); VENCATESAN (Jayshree) (New Delhi Rupa & Co., 2008)
Western Ghats-Biodiversity, People, Conservation covers a wide range of topics including the geological history, origin and evolution of biodiversity. It highlights the diversity of life in the region starting from micro-organisms and moves on to analyse and discuss the ways in which the different species of plants and animals have naturally assembled to form living communities. The long human history of the region and the way it has influenced the biodiversity has also been described. Not only that, it also discusses the future of the Western Ghats and its biodiversity in the light of the ever-increasing human pressures on land and water. The book has been written in a unique, simple style avoiding technical jargons so that it appeals to the general reader. It contains a large number of illustrations and unique photographs of the region that will enable the readers to identify the plants and animals discussed in the book. In short, the book is aimed at the layman as well as the serious student who wishes to learn about the rich biological wealth and ecological history of one of the Earth s last remaining tropical wilderness.
Keywords: India-Western Ghats; Biodiversity; Human Ecology; Biodiversity Conservation